Resource-based view strategy as a determinant of business performance moderated by market orientation in MSMEs culinary sector in Medan city - Bella Marisa Putri; Ani Murwani Muhar; Zuwina Miraza (Manajemen dan Bisnis, 2022)
The purpose of this research is to know the business performance can be achieved through Resource Based View Strategy by applying flexibility, supply chain integration, organization capability to market orientation in culinary sector business in Medan. Data collection using questionnaires (Google Form) for each variable, on 88 MSMEs culinary sector in Medan city with the characteristics of small to medium businesses and already applying supply chain integration. The data is analyzed using multiple linear and moderated regression analysis (MRA) techniques. The results showed that flexibility had no positive effect on business performance. However, supply chain integration and organization capability had a positive effect on business performance. Flexibility and supply chain integration positively affect business performance moderated by market orientation. At the same time, organization capability does not positively affect business performance moderated by market orientation.